Characterization of a Hygro-Regulated Wall Base Ventilation System for Treatment of Rising Damp - V. P. Freitas (2012)
The treatment of rising damp in the walls of historical buildings is very complex, due to the thickness and heterogeneity of the walls. The techniques traditionally used for dealing with this problem (such as watertight barriers, injection of hydrofuge products, etc.) have sometimes proved ineffective, and that is why it is necessary to find a new approach. In recent years, the Building Physics Laboratory at the Faculty of Engineering, University of Porto has been conducting experimental research on the effectiveness of the wall base ventilation system, using natural or mechanical higro-regulate systems to reduce the level of the damp area. This experimental research and the simulations that were performed, clearly show that wall base ventilation is a system with potential. This paper presents the characterization of the hygro-regulated systems' operation based on experimental studies developed in laboratory, which allowed the influence of the velocity of the air, condensation risk and the possibility of salt crystallization.